ANALYSIS STUDY OF REINFORCED CONCRETE FRAME STRUCTURES WITH INFILL WALLS DUE TO LATERAL LOADS USING THE EQUIVALENT DIAGONAL STRUT AND FINITE ELEMENT METHOD - Suku, Yohanes Laka; Radja, Veronika Miana (Journal of Applied Engineering Science, 2025)
The analysis study of reinforced concrete frame structures with infill walls due to lateral loads using the equivalent diagonal strut (EDS) method proposed by Saneinejad & Hobbs (1995) aims to determine the accuracy in the analysis. This study began by evaluating reinforced concrete frame structures with infill walls as a result of the experiments of Mehrabi et al. (1994) using the finite element method (FEM). Then FEM analysis was carried out on the reinforced concrete frame structure by varying the hinf/linf of the infill walls with a ratio of 0.50, 0.67, 1.00 and 1.50. Next, the FEM analysis results will be evaluated using the EDS method. The analysis results show that the EDS method can predict the maximum lateral load close to the experimental results and FEM analysis. In the analysis using the EDS method, the friction coefficient (µ) and basic shear stress (ν) parameters greatly influence the strength of the infill wall.